PHYSICOCHEMICAL AND NUTRITIONAL CHARACTERISTICS OF DIFFERENT CASSAVA VARIETIES CULTIVATED IN NAMPULA PROVINCE - Rosa, Porfírio Américo Nunes; Tanleque-Alberto, Fernando João; Miguel, Cristovão João; da Costa, José Jorge; Leal, Maria Alice Tavares Chaves; Rúbio, Amilton Martins; Salimo, Epifânia Sidónio Alberto; Gemusse, Renato Pedro (Seven Editora, 2026)
Cassava (Manihot esculenta Crantz) is one of the main staple foods in Mozambique; however, variability among varieties may affect nutritional quality, food safety, and processing potential, representing a challenge for its proper utilization. This study aimed to evaluate the physicochemical and nutritional characteristics of five cassava varieties cultivated in Nampula Province (Badje, Mokhalana, Napirithe, Nziva, and Técnico). Mature roots were collected and laboratory analyses were performed for moisture, ash, pH, titratable acidity, cyanide, β-carotene, lycopene, and total solids, with statistical treatment by ANOVA. Moisture ranged from 51.91 ± 1.54% (Badje) to 58.35 ± 0.96% (Napirithe), while ash content varied between 1.06 ± 0.08% (Mokhalana) and 5.08 ± 0.53% (Napirithe). pH ranged from 6.64 ± 0.01 (Napirithe) to 7.79 ± 0.15 (Mokhalana), and titratable acidity ranged from 3.94 ± 0.07% (Napirithe) to 7.97 ± 0.08% (Técnico). β-carotene contents were highest in Nziva (11.52 ± 0.15 µg/g) and Técnico (20.81 ± 0.27 µg/g), while lycopene ranged from 6.99 ± 0.09 µg/g (Mokhalana) to 11.18 ± 0.45 µg/g (Técnico). Cyanide levels ranged from 3.70 ± 0.48 mg/g (Nziva) to 5.09 ± 0.02 mg/g (Técnico), remaining below critical limits for safe consumption after proper processing. It is concluded that varietal selection based on physicochemical and nutritional parameters is a relevant strategy to optimize food, industrial, and nutritional use of cassava in Nampula.